2017
DOI: 10.1186/s12933-017-0565-z
|View full text |Cite
|
Sign up to set email alerts
|

Westernization of lifestyle affects quantitative and qualitative changes in adiponectin

Abstract: BackgroundAlthough Japanese–Americans and native Japanese share the same genetic predispositions, they live different lifestyles, resulting in insulin resistance in Japanese–Americans. We investigated whether the quantitative and qualitative changes in adiponectin (APN) due to differences in lifestyle contribute to the development of insulin resistance.MethodsWe evaluated 325 native Japanese in Hiroshima, Japan and 304 Japanese–Americans in Los Angeles, the United States, who were aged between 30 and 70 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Odoribacter is also reported to produce sulfobacin B; sulfobacin B treatment is reported to suppress lipopolysaccharide‐induced inflammation in mice. Considering that the levels of C‐reactive protein, an inflammatory marker, are reportedly lower in native Japanese than in Japanese‐Americans, Odoribacter ‐produced sulfobacin B might exert an anti‐inflammatory effect and partially contribute to improved insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Odoribacter is also reported to produce sulfobacin B; sulfobacin B treatment is reported to suppress lipopolysaccharide‐induced inflammation in mice. Considering that the levels of C‐reactive protein, an inflammatory marker, are reportedly lower in native Japanese than in Japanese‐Americans, Odoribacter ‐produced sulfobacin B might exert an anti‐inflammatory effect and partially contribute to improved insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…We undertook a medical survey targeting Japanese people, and their descendants, who emigrated to the USA (the Hawaii‐Los Angeles‐Hiroshima Study) since 1970. It was inferred that Japanese‐Americans with an American lifestyle in Hawaii or Los Angeles had a higher degree of insulin resistance, as well as a higher prevalence of diabetes mellitus and metabolic syndrome than native Japanese with a Japanese lifestyle in Hiroshima.…”
Section: Introductionmentioning
confidence: 99%
“…Higher circulating adiponectin levels were also associated with a beneficial development of heart rate variability over 5 years in T2DM representing improved cardiovascular autonomic function [ 42 ]. Comparing a native Japanese population with Japanese-American people revealed lower serum adiponectin and increased measures of inflammation in the later indicating that westernization of lifestyle may affect adiponectin which in turn might promote development of insulin resistance [ 43 ]. Strengthening the role of adiponectin in T2DM, an increase of circulating adiponectin in response to anti-diabetic treatment has been reported [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The 2010 survey carried out in Los Angeles compared serum total adiponectin levels between native Japanese people and Japanese Americans in terms of their glucose tolerance status; namely, NGT, impaired glucose tolerance and diabetes mellitus groups 13 . The serum total adiponectin levels were significantly lower in Japanese Americans than in native Japanese people in the NGT and impaired glucose tolerance groups, but not in the diabetes mellitus group.…”
Section: Smentioning
confidence: 99%
“…The serum total adiponectin levels were significantly lower in Japanese Americans than in native Japanese people in the NGT and impaired glucose tolerance groups, but not in the diabetes mellitus group. Furthermore, among the participants included in the report 13 , those with NGT were divided into a non-obese group (a BMI of <25 kg/m 2 ) and an obese group (a BMI of ≥25 kg/m 2 ): the number of native Japanese and Japanese Americans in the non-obese and the obese groups were 190 and 57, and 186 and 51, respectively. Additionally, insulin resistance between native Japanese people and Japanese Americans was compared, and the results showed that Japanese Americans, even in the non-obese group, had high homeostasis model assessment of insulin resistance levels and low Matsuda Index levels (Figure 4).…”
Section: Smentioning
confidence: 99%